DIAGNOSIS OF SKIN DISEASES IN TODDLERS USING NAÏVE BAYES AND FORWARD CHAINING METHODS - Sidik Rahmatullah; Rima Mawarni (IJISCS (International Journal of Information System and Computer Science), 2021)
The Center for Public Health is a functional organizational unit that implements health care that is thorough, integrated, evenly acceptable, and affordable to the community. The purpose of this research is to create an Expert System Application to detect skin diseases in toddlers according to the data in the public health center. The system development method used is the Extreme Programming (XP) method with working stages including planning, design, coding, and testing. The system is designed using Unified Modeling Language (UML) which includes use cases, activity diagrams, and chart classes, the software used is PHP (Hypertext Preprocessor) with MySQL databases and uses the Naïve Bayes and Forward Chaining methods. The end result of the creation of this App is to make it easier for users or the public in detecting skin diseases for toddlers.